Entrepreneurial ecosystems, entrepreneurial activity and economic growth: new evidence from European regions. Issue 8 (2nd August 2020) - Content, Jeroen; Bosma, Niels; Jordaan, Jacob; Sanders, Mark
ABSTRACT: A latent class model is applied to allow entrepreneurial ecosystems (EEs) to influence the effect of entrepreneurial activity on growth in European Union regions. Using this methodology, clusters of regions that differ significantly in their relationship between entrepreneurial activity and growth are identified. This is consistent with the hypothesis that EEs affect this relationship. Subsequently, cluster membership is related to regional characteristics representing a range of components of EEs and marked differences in a variety of these regional characteristics are found. Taken together, the results support the notion that EEs help shape the impact of entrepreneurial activity on growth.